2021
DOI: 10.1186/s40634-021-00368-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of contemporary lateral augmentation techniques in primary ACL reconstruction: a systematic review and meta-analysis

Abstract: Purpose The purpose of this investigation was to systematically review the contemporary literature to determine if a lateral augmentation (LA) added to an Anterior Cruciate Ligament Reconstruction (ACLR) provides better clinical and patient reported outcomes compared to an isolated ACLR. Methods A systematic review and meta-analysis was performed according to the Preferred Reporting Items for Systematic reviews and Meta-analyses (PRISMA) criteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 65 publications
(261 reference statements)
0
14
0
Order By: Relevance
“…21 The recording of additional surgical details such as graft diameter/size, ligament augmentation, lateral extra-articular tenodesis, or anterolateral ligament reconstruction may also be of value, given their recent association with outcomes. 1,10,15,16,24,26,42,52 Clinical examination and rehabilitation information such as preoperative knee laxity grade 25,43 could be obtained via third-party sources such as physical therapists or via natural language processing of patient chart notes. 49 Finally, the KOOS may not be the most appropriate patient-reported outcome tool for the patient population, and an alternative measurement of patient function, such as the baseline Marx activity level, could be considered for inclusion in registries moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…21 The recording of additional surgical details such as graft diameter/size, ligament augmentation, lateral extra-articular tenodesis, or anterolateral ligament reconstruction may also be of value, given their recent association with outcomes. 1,10,15,16,24,26,42,52 Clinical examination and rehabilitation information such as preoperative knee laxity grade 25,43 could be obtained via third-party sources such as physical therapists or via natural language processing of patient chart notes. 49 Finally, the KOOS may not be the most appropriate patient-reported outcome tool for the patient population, and an alternative measurement of patient function, such as the baseline Marx activity level, could be considered for inclusion in registries moving forward.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent systematic review and metaanalysis, Beckers et al found a significant reduction in graft ruptures in patients treated with ACLR and lateral augmentation (3%) compared to isolated ACLR (12%) and rotational laxity significantly higher in isolated ACLR (14% vs. ACLR + LA (6%). 71 In another recent systematic review, Littlefield et al reported lower ACL graft failure rates for combined ACLR/ALLR (0.0% -15.7%) when compared to isolated ACLR patients (7.4% -21.7%), whereas Kunze et al reported a failure rate of 2.7%-11.1%, and significant improvement in the IKDC, Lysholm, and Tegner outcome scores postoperatively. 3,70 Recent systematic reviews showed that ACLR + ALLR improved patient-reported outcomes at short-term follow-up compared to those who underwent isolated ACLR.…”
Section: Outcomementioning
confidence: 98%
“…Current literature suggests that combined ACLR with ALLR or LET can improve clinical outcomes and decrease the possibility of ACL graft failure compared to isolated ACLR[ 43 ]. Beckers et al [ 68 ] observed that both LET and ALLR during ACLR provided superior Lysholm Score and reduced ACL re-rupture rate. Na et al [ 69 ] in a systematic review found that ALLR or LET along with ACLR were related to superior subjective IKDC, Tegner and Lysholm scores than isolated ACLR.…”
Section: Clinical Evidencementioning
confidence: 99%